Final report of grit blasting and metal spraying trials carried out at H. M. Dockyard, Devonport - Apps, R. L. (College of Aeronautics, 1966)
Mild steel surfaces that are to be protected by aluminium or zinc spray coatings are generally prepared by blasting with chilled iron angular grit. Previous work1had shown that a relationship exists between the grit blasting conditions (at least in terms of blasting angle and grit condition), the reflectivity of the blasted surface and the bond strength of a spray coating of aluminium on the blasted surface. An instrument has been developed that assesses the suitability of a blasted surface for subsequent spraying by measuring the reflectivity and has proved reasonably successful under laboratory conditions. The present need is to ascertain the performance of this reflectivity meter under shop and site conditions. The opportunity to carry out such tests at H.M. Dockyard, Devonport, was offered by the Ministry of Defence and a series of tests was made on 16th June, 1965.